2001
DOI: 10.1002/xrs.479
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of a secondary target XRF setup at different operational tube voltages

Abstract: An algorithm was developed that allows a theoretical step-by-step study of secondary target XRF setups for different combinations of anode materials, secondary targets and operating tube voltages. By use of three different descriptions of x-ray tube spectral distributions, the qualitative and quantitative characteristics of the x-ray beam after the secondary target are examined. Calculations are presented for different combinations of anode material and secondary target such as Y-Mo, Mo-Mo, Rh-Mo and W-Mo. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For the secondary target thickness experiment, the secondary targets chosen to be examined were copper (Cu), molybdenum (Mo), and tin (Sn). Cu and Mo are two common metallic secondary targets, while Sn was chosen to see if the trend was consistent at higher atomic numbers. The voltage was chosen to be 30 kV for the Cu trial, and 50 kV for the Mo and Sn, which allowed for significant X‐ray production in the energy range of interest, while avoiding the production of higher energy X‐rays that are much more likely to scatter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the secondary target thickness experiment, the secondary targets chosen to be examined were copper (Cu), molybdenum (Mo), and tin (Sn). Cu and Mo are two common metallic secondary targets, while Sn was chosen to see if the trend was consistent at higher atomic numbers. The voltage was chosen to be 30 kV for the Cu trial, and 50 kV for the Mo and Sn, which allowed for significant X‐ray production in the energy range of interest, while avoiding the production of higher energy X‐rays that are much more likely to scatter.…”
Section: Methodsmentioning
confidence: 99%
“…[4] Because these metallic secondary targets play such a large role in polarized EDXRF, it is advantageous to optimize their characteristics. [6,8,9] In order to optimize the use of these secondary targets, it is necessary to investigate the relationship between the material of choice, its thickness, and the amount of polarized and fluoresced X-rays produced for given X-ray tube exposure parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to previous studies, the weaker relationship observed in this study was not influenced by the instrument's accuracy as the recovery for Rb was within the benchmark of 100% ± 20% (Table 1). Moreover, the benchtop EDXRF used for the current study is equipped with secondary targets at Cartesian geometry, improving the sensitivity of trace elements such as Rb by reducing background intensity; thus, it is more sensitive/ accurate and precise than the portable XRF (Bisgård et al 1981;Zarkadas et al 2001;Manousakas et al 2018).…”
Section: Selection Of Elements For Calibration Modelsmentioning
confidence: 99%
“…The fact that the scatter peak intensity in XRF is related to mean atomic number is hardly novel, but Ertugrul 44 reported a standard curve of atomic number versus the intensity ratio of coherently to incoherently scattered radiation and compared experimental and calculated values. Zarkadas et al 45 looked specifically at optimising secondary target excitation using different combinations of tube anode-secondary target and different tube operating potentials. They produced an algorithm to describe the secondary target excitation characteristics that was claimed to be applicable to any such instrumentation of this design.…”
Section: Matrix Correction and Calibration Proceduresmentioning
confidence: 99%